Shot in America : television, the state, and the rise of Chicano cinema - Noriega, Chon A., 1961- (Minneapolis : University of Minnesota Press, 2000)
Noriega offers a compelling and detailed description of an enormous body of work by Chicano media makers against the backdrop of Chicano social movements, politics, and activism over a forty-year period--an extraordinary exposition of the civil rights movement, media reform activities, and public affairs programming that constitutes the prehistory of independent and minority cinemas. 2000 Choice Outstanding Academic Title.
"No revolutions without poets": Chicano poetic consciousness -- Setting the stage: social movements, the state, and mass media -- "The stereotypes must die": social protests and the Frito Bandito -- Regulating Chico: the irony of approaching a state-supported industry -- Grasping at the public airwaves: the FCC and the discourse of violence -- Training the activists to shoot straight: a political generation in U.S. cinema -- "Our own institutions": the geopolitics of Chicano professionalism -- This is not a border: from social movement to digital revolution.
Filmography: pages 251-255.
Includes bibliographical references (pages 257-285) and index.
Online resource; title from PDF title page (JSTOR, viewed October 15, 2015).
JSTOR
Keywords: Mexican Americans in motion pictures; Mexican Americans on television; Mexican Americans in the motion picture industry; Américains d'origine mexicaine au cinéma.; Américains d'origine mexicaine à la télévision.; Américains d'origine mexicaine dans l'industrie cinématographique.; PERFORMING ARTS -- Film & Video -- History & Criticism; Mexican Americans in motion pictures; Mexican Americans in the motion picture industry; Mexican Americans on television; Filmwirtschaft; Fernsehen; Film; USA; Chicanos